The Influence of Service Quality and Infrastructure on Student Satisfaction and Loyalty at SMPIT Muhammadiyah Pangkalan Kerinci - Elvi Sri Rizkiyani; Gusnardi; Gimin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
Student loyalty reflects a strong commitment to their school, demonstrated through continued support for the services provided and influencing prospective students to enroll. This study aims to analyze the effect of service quality and school facilities on student loyalty, with student satisfaction serving as a mediating variable. The research was conducted at SMPIT Muhammadiyah Pangkalan Kerinci using a quantitative approach. The sampling technique employed was a saturated sample, involving the entire population of 34 students. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that service quality and school facilities significantly influence student satisfaction, which in turn affects student loyalty. These findings emphasize that improving service quality and providing adequate facilities are essential in fostering student satisfaction and loyalty. The practical implication of this study suggests that schools should focus on enhancing educational services and infrastructure to build stronger student engagement and commitment.